Experience in Providing Medical Assistance to the Population of the Amur Region Exposed to the Effects of the Flood - N. L. Tezikov; M. P. Gulevich; N. A. Lipskaya; Yu. A. Natykan; N. N. Korotaeva (Проблемы особо опасных инфекций, 2014)
Medical assistance to individuals residing in the flooded areas of the region was delivered on a priority basis throughout the health care institutions on the territorial-division principle, at the temporal accommodation sites, further on - long-term stay centers, 24-hours a day. Determined was the amount of means for specific prophylaxis, immunized was the contingent under risk, stocked up were pharmaceutical preparations, medical products and consumables. Therewith, carried out therapeutic, medical-preventive operations turned out to be on-time and sufficient for providing essential complex of medical assistance to the exposed population in the devastated areas.